Olive Mill Waste Enhances α-Glucan Content in the Edible Mushroom Pleurotus eryngii - Avni, Sharon (Int J Mol Sci, 2017)
Mushroom polysaccharides are edible polymers that have numerous reported biological functions; the most common effects are attributed to β-glucans. In recent years, it became apparent that the less abundant α-glucans also possess potent effects in various health conditions. Here we explore several Pleurotus species for their total, β and α-glucan content. Pleurotus eryngii was found to have the highest total glucan concentrations and the highest α-glucans proportion. We also found that the stalks (stipe) of the fruit body contained higher glucan content then the caps (pileus). Since mushrooms respond markedly to changes in environmental and growth conditions, we developed cultivation methods aiming to increase the levels of α and β-glucans. Using olive mill solid waste (OMSW) from three-phase olive mills in the cultivation substrate. We were able to enrich the levels mainly of α-glucans. Maximal total glucan concentrations were enhanced up to twice when the growth substrate contained 80% of OMSW compared to no OMSW. Taking together this study demonstrate that Pleurotus eryngii can serve as a potential rich source of glucans for nutritional and medicinal applications and that glucan content in mushroom fruiting bodies can be further enriched by applying OMSW into the cultivation substrate.